The Impact of Remote Working on Employee Productivity During COVID-19 in Indonesia: The Moderating Role of Job Level and the Influence of Cultural Adaptability - Jamaluddin (Yayasan Ghalih Pelopor Pendidikan, 2025)
The COVID-19 pandemic has reshaped workplace dynamics globally, with remote work becoming a necessity. This study investigates the determinants of employee productivity in Indonesia’s remote work settings, focusing on workload, job satisfaction, work-life balance, social support, and cultural adaptability. Data from 150 respondents across various industries were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that job satisfaction (β = 0.42, p < 0.001) and work-life balance (β = 0.35, p < 0.001) have the strongest impacts on productivity, followed by cultural adaptability (β = 0.38, p < 0.001) and social support (β = 0.29, p < 0.001). Interestingly, job level does not significantly moderate these relationships, indicating consistency across organizational hierarchies. The results highlight the importance of addressing cultural dynamics, workload balance, and social support systems to enhance productivity. Practical implications include strategies for improving remote work effectiveness in culturally diverse environments.